Baicalein Prevents Fructose-Induced Hepatic Steatosis in Rats: In the Regulation of Fatty Acid De Novo Synthesis, Fatty Acid Elongation and Fatty Acid Oxidation - Li, Pan; Zhang, Ruoyu; Wang, Meng; Chen, Yuwei; Chen, Zhiwei; Ke, Xiumei; Zuo, Ling; Wang, Jianwei (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD), ranging from simple steatosis to non-alcoholic steatohepatitis (NASH), hepatic fibrosis and even hepatocellular carcinoma, is a liver disease worldwide without approved therapeutic drugs. Baicalein (BAL), a flavonoid compound extracted from the Traditional Chinese Medicine (TCM) Scutellariae Radix (Scutellaria baicalensis Georgi.), has been used in TCM clinical practice for thousands of years to treat liver diseases due to its “hepatoprotective effect”. However, the underlying liver-protecting mechanisms remain largely unknown. Here, we found that oral administration of BAL significantly decreased excess serum levels of triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), aspartate aminotransferase (AST) as well as hepatic TG in fructose-fed rats. Attenuation of the increased vacuolization and Oil Red O staining area was evident on hepatic histological examination in BAL-treated rats. Mechanistically, results of RNA-sequencing, western-blot, real-time quantitative PCR (RT-qPCR) and hepatic metabolomics analyses indicated that BAL decreased fructose-induced excessive nuclear expressions of mature sterol regulatory element-binding protein 1c (mSREBP1c) and carbohydrate response element-binding protein (ChREBP), which led to the decline of lipogenic molecules [including fatty acid synthase (FASN), stearoyl-CoA desaturase 1 (SCD1), elongation of very long chain fatty acids 6 (ELOVL6), acetyl-CoA carboxylase (ACC)], accompanying with the alternation of hepatic fatty acids composition. Meanwhile, BAL enhanced fatty acid oxidation by activating AMPK/PGC1α signaling axis and PPARα signal pathway, which elicited high expression of carnitine palmitoyl transferase 1α (CPT1α) and Acyl-CoA oxidase 1 (ACO1) in livers of fructose-fed rats, respectively. BAL ameliorated fructose-induced hepatic steatosis, which is associated with regulating fatty acid synthesis, elongation and oxidation.